THE ROLE OF BRAZIL’S “MARCO CIVIL DA INTERNET” LAW IN THE FIELD OF INTERNET USE AND INFORMATION EXCHANGE - Ilkhombekov Jasurbek Ilkhombek ugli (Modern American Journals, 2026)
This scientific article provides a detailed analysis of Brazil’s law on Internet regulation. Today, the Internet has become an integral part of social, political, economic, and cultural processes. The acceleration of information flows, the expansion of global communications, and the development of democratic values are directly linked to the Internet. At the same time, issues such as the protection of personal data, information security, and network neutrality remain highly relevant in the process of Internet usage. This article scientifically analyzes the role of Brazil’s 2014 law “Marco Civil da Internet” in public life, its comparative aspects with international experiences, as well as its significance in the field of Internet use and information exchange. The study mainly focuses on the specific features of Brazil’s approach to Internet regulation. In addition, the article examines the importance of the Internet in the process of information exchange, its differences from other information resources, its advantages, and its legal significance.
Keywords: Information, Internet, Brazil, “Marco Civil da Internet”, Dilma Rousseff, “Internet Constitution”, Ministry of Justice of Brazil, Edward Snowden, Tim Berners-Lee, Internet technologies, privacy, personal data.